Las habilidades sociales y las conductas asertivas de los estudiantes del primer año de bachillerato paralelo a, de la Unidad Educativa Fiscomisional Nuestra Señora del Rosario cantón Catamayo, 2020-2021. - Lady Thalia Aguilar Vicente, Lady Thalia (2022)
The research work entitled: THE SOCIAL SKILLS AND ASSERTIVE BEHAVIORS OF THE STUDENTS OF THE FIRST YEAR OF HIGH SCHOOL PARALLEL A, OF THE FISCOMISSIONAL EDUCATIONAL UNIT NUESTRA SEÑORA DEL ROSARIO CANTON CATAMAYO, 2020-2021, aimed to analyze the relationship between social skills and the assertive behaviors of the students of the first year of parallel high school A, a quantitative approach was used; descriptive, non- experimental and cross-sectional design. The Social Interaction Skills Questionnaire by Inés Monjas (1994) and the Multidimensional Assertiveness Scale by Mirtha Flores (2004) were applied to a sample of 20 students. Of the results obtained in relation to the evaluation of the skills of those investigated, 55% show a high level of basic skills, likewise 65% show skills to make friends, in the same percentage they maintain conversational skills and with 65% skills to interpersonal problem solving at a moderate level; while the results of assertive behavior, it is found that at the same average level, those investigated show 70% indirect assertiveness behavior, for 60% they show non- assertive behavior and while 55% show a high level of assertiveness. assertive behavior. From the results obtained from the dimensions of social skills, it is concluded that a good percentage at a high level have developed basic skills and it is very important to know the percentage of 65% at a moderate level, skills to make friends, conversational skills and interpersonal problem solving. and it can be evidenced that the students show medium levels in assertive behaviors, indirect assertiveness and non-assertive behaviors; To face this problem, a psychoeducational proposal is presented to strengthen social skills and maintain assertive behaviors through assertive techniques. Keywords: Social Skills, Assertive Behavior, Adolescents.